2018
DOI: 10.4236/ajps.2018.93038
|View full text |Cite
|
Sign up to set email alerts
|

Indolbutyric Acid and Time of the Year Influence on Rooting of Chrysanthemum Cuttings

Abstract: The objective of this study was to analyze the effect of the seasons and indol butyric acid (IBA), as well as the preparation of IBA solutions on rooting growth of "Fine Time" chrysanthemum cuttings. The first experiment was arranged in a 4 × 2 factorial scheme: IBA concentrations (0, 1000, 2000 and 3000 mg·L −1 ) during summer and winter with 4 replicates of two pots and six cuttings per pot. In the second experiment, the storage of IBA solution (1000 mg·L −1 ) at 15˚C was studied with four replicates of 10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The cuttings of Coleus red were treated with diluted lanolin in greenhouses, its root formation is not affected [25]. However, a finding has shown that pure lanolin, when applied on chrysanthemum cuttings in summer, interferes with the rooting of cuttings [49]. These different effects of lanolin on the rooting of cuttings may be related to concentration of lanolin and environment of the treatment.…”
Section: Lanolin Promotes Anthocyanin Biosynthesis In 'Zaosu' Pear Fruitmentioning
confidence: 99%
“…The cuttings of Coleus red were treated with diluted lanolin in greenhouses, its root formation is not affected [25]. However, a finding has shown that pure lanolin, when applied on chrysanthemum cuttings in summer, interferes with the rooting of cuttings [49]. These different effects of lanolin on the rooting of cuttings may be related to concentration of lanolin and environment of the treatment.…”
Section: Lanolin Promotes Anthocyanin Biosynthesis In 'Zaosu' Pear Fruitmentioning
confidence: 99%